Using community health workers:. Issue 1 (May 2015) - MAES, KENNETH; CLOSSER, SVEA; VOREL, ETHAN; TESFAYE, YIHENEW; Maes, Kenneth
<x xml:space="preserve">Abstract</x> In this article, we use semistructured interviews and documents produced by Ethiopian government officials and international health donors to examine two key features of the nation's community health worker (CHW) program: (1) the process and criteria of selecting community health workers; and (2) policies, rhetoric, and experiences of payment and empowerment. We examine these from the varied perspectives of district health officials, Health Extension Workers, and leaders and members within Ethiopia's so‐called Women's Development Army, whom we interviewed during 2012–14. According to national policymakers and policy documents, the goals of the Women's Development Army are twofold: first, to reduce mortality and second, to produce "model" women, who discipline themselves and their neighbors to enact healthy behaviors. The Army is supposed to simultaneously "empower" these women to be more autonomous from husbands and more active in development‐oriented work. Yet one of the key criteria sought by district‐level health officials—willingness to "accept what we teach them and implement what we tell them"—highlights that Army leaders are to remain subordinate to government health officials. Many female members of the Women's Development Army expressed ambivalence about their selection, particularly as the position was unpaid. Some questioned why women were expected to volunteer when men had previously been paid to do similar work. These data emphasize the differences in goals, aims, and experiences among various actors involved in CHW programs, and the need for researchers to address whether or not respondents are comfortable to express perspectives that might question dominant goals and discourses.